Demographic, clinical, and laboratory characteristics of two cases of clinically isolated syndrome in a tertiary care teaching hospital - S. Ramesh Kannan; Shashikala Nair; Nayyar Iqbal; Priya Thomas; Shobana Sundaram (Journal of Current Research in Scientific Medicine)
Most of the patients with multiple sclerosis present initially as radiologically isolated syndrome followed by clinically isolated syndrome (CIS). To prevent long-term progression to multiple sclerosis, it is essential to differentiate CIS from other neurological disorders. We present two cases that were clinically diagnosed to have CIS. The patients were subjected to blood tests such as vasculitic markers, urine tests, cerebrospinal fluid (CSF) analysis, magnetic resonance imaging (MRI), and visual evoked potentials (VEP). Both the patients were middle-aged, a male and a female, and revealed evidence of demyelinating lesions of the optic nerve, subcortical, brainstem, and spinal cord in the VEP and MRI. The male patient had CSF being negative for oligoclonal bands and revealed no evidence of seromarkers such as antinuclear antibody, anti-myelin oligodendrocyte glycoprotein, and anti-aquaporin protein-4 antibodies which could explain the MRI findings. The female patient revealed demyelinating subcortical frontal and parietal lesions. She had prolonged P100 latencies suggesting optic nerve demyelination. We suggest to have a high index of suspicion about demyelinating disorders in tertiary care hospitals in the developing world, and to create awareness among the referring physicians which could help them in the early identification of patients with CIS, and prevent conversion of these patients with CIS to clinically definite multiple sclerosis with severe morbidity.